Samarium dienolate mediated stereoselective synthesis of anti-1,3-diol monoesters via aldol-Tishchenko reaction - Vichai Reutrakul (2018)
The reaction of an (E)-samarium dienolate, generated by the regioselective reductive cleavage of a phenylsulfonyl activated cyclopropyl ketone with samarium(II) iodide, with aliphatic and aromatic aldehydes gives the 2-substituted anti-1,3-diol monoester derivatives, stereoselectively, in good to excellent yields. The results represent the first report of a dienolate in the aldol-Tishchenko reaction and also provide an optically active polyol with (R)-glyceraldehyde. © 2006 Elsevier Ltd. All rights reserved.